Pickering polymerization of styrene stabilized by starch-based nanospheres. Issue 19 (25th April 2016) - Pei, Xiaopeng; Tan, Ying; Xu, Kun; Liu, Chang; Lu, Cuige; Wang, Pixin
Abstract : Pickering polymerization of styrene stabilized by starch-based nanospheres to synthesize composite particles with different morphologies is reported. Abstract : Here, we present a novel nanoparticle derivate from natural polysaccharide as a stabilizer for the Pickering polymerization of styrene. In this process, amphiphilic starch-based nanospheres (SNPs) were fabricated from starch octenyl succinic ester through a nanocoprecipitation process as a Pickering stabilizer. The effects of the SNP concentration, size and pH value on the Pickering polymerization are investigated in detail. The polystyrene (PS) particle morphology transforms from bare PS particles to raspberry-like structures with an increase in the SNP content. The linear relationship between the inverse diameter of the PS particles and the SNP content allows for an estimation of the coverage of SNPs on the PS particle surface. Moreover, the size of the PS particles can be regulated by the SNP size. The microstructure of the PS particles can also be regulated by the pH value of the reaction medium. Finally, a possible mechanism for the formation of the PS particles with different morphologies is proposed.